A CASE STUDY ON THE EFFICACY OF HERBAL MEDICINE AND DIETARY INTERVENTIONS IN THE ALTERNATIVE MANAGEMENT OF GALLSTONE DISEASE - Vijayarajah Thanushiyan; B. Uthayanan; M.H.K. Faiz; S. Uthayanan (The Bioscan, 2025)
Gallstone disease, or cholelithiasis, affects 10-15% of adults, often asymptomatic but with potential complications. Gallstones form due to factors like gallbladder dysmotility and hormonal changes. This case study describes a patient with acute abdominal pain, tenderness in the 11th intercostal region, and gallstones causing obstruction. Initial treatment included Siriyalnangai (Andrographis paniculata) tablets (300 mg, twice daily for two weeks) due to their potential to stimulate the Farnesoid X Receptor (FXR) and promote gallstone dissolution. In the third week, the patient consumed green apple juice (1 liter daily) to soften bile stones through its phenolic content, reducing bile acids and bilirubin. After six days, the patient was hospitalized, maintaining a diet of green apple juice, basmati rice, and steamed vegetables. On the last day, Epsom salt doses were given to stimulate bowel movements. Stool analysis showed light green, semisolid particles, and the patient’s symptoms resolved, with ultrasound revealing only a small, non-obstructive gallstone. This regimen, combining Siriyalnangai, green apple juice, and Epsom salt, highlights a promising non-surgical approach to gallstone management, though further research is essential to validate its effectiveness and establish protocols.